2015
DOI: 10.1016/j.ultsonch.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasonic treatments on the polyphenol and antioxidant content of spinach extracts

Abstract: The objective was to test ultrasound treatments on spinach leaves during extraction, and conventional 11 extraction was used as a control. The effects of different combinations of the ultrasonic water bath factors 12 tested on phenolic compound yields included frequency (37 and 80 kHz), exposure time (5, 10, 15, 20, 13 25, and 30 min), temperature (30, 40, and 50 °C), and ultrasonic power (30, 50, and 70 %). The best 14 conditions for extraction yields were ultrasonic frequency of 37 kHz, extraction time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 36 publications
(1 reference statement)
9
77
1
Order By: Relevance
“…This result confirms that the plant extracts with the highest amount of phenolic content will be more effective at scavenging free radicals. These findings were in an agreement with Altemimi et al [27] and Fernandez-Gutierrez [28], who discovered that the phenolic profile was considered very important to show the relation between the abovestated categories.…”
Section: Resultssupporting
confidence: 92%
“…This result confirms that the plant extracts with the highest amount of phenolic content will be more effective at scavenging free radicals. These findings were in an agreement with Altemimi et al [27] and Fernandez-Gutierrez [28], who discovered that the phenolic profile was considered very important to show the relation between the abovestated categories.…”
Section: Resultssupporting
confidence: 92%
“…However, results for other indices of extraction efficiency clearly exhibited that lower ultrasonic frequency was more effective compared to higher frequency. Similar findings were reported for polyphenol recovery using ultrasonication from spinach (Altemimi et al ., ), where the ultrasonic bath operating at 37 kHz was more effective than 80 kHz at temperature–power–time combination of 40 °C, 50% and 30 min, with regard to extraction yield, total phenols and % DPPH inhibition. Furthermore, higher intensity/power ultrasound effectiveness over lower intensity/power has also been testified for recovery of protein from soy flakes (Karki et al ., ) and glycoalkaloids from potato peel (Hossain et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Chan, Yusoff, Ngoh, and Kung () reported that the yield of phenolic compounds increased when the temperature increased from 40°C to 70°C, whereas Teh and Birch () found TPC yield to increase with increase from 40°C to 50°C. However, at 60°C, extraction yield in flax and canola seed cake extracts were reported to decrease (Altemimi, Choudhary, Watson, & Lightfoot, ) probably due to the destruction of phenolic compounds.…”
Section: Resultsmentioning
confidence: 99%